Food Expenditure and Diet Diversity Score are Predictors of Household Food Insecurity among Low Income Households in Rural District of Kelantan Malaysia - Ihab, A.N.; Rohana, A.J.; Manan, W.M. Wan; Suriati, W.N. Wan; Zalilah, M.S.; Rusli, A.M. (Pakistan Journal of Nutrition, 2012)
Food insecurity has always been associated with low purchasing power and inadequate dietary intake in terms of quality and quantity. The aim of this study is to identify the relationship between household food insecurity, food expenditure and diet diversity in low income households in rural Malaysia. A cross-sectional survey of low-income households was conducted in 223 households of mothers aged 18 to 55 years old. Non-lactating and non-pregnant mothers were purposively selected. A questionnaire was administered. Items on socio-demographic characteristics and food expenditures of eight food groups were rated on the Radimer/Cornell scale. Diet diversity scores were analyzed from the food frequency questionnaire. Approximately 83.9% of caretaker respondents revealed that they and the members of their households had experienced periods of food insecurity in the 12 months prior to the interview. Of the 83.9%, 29.6% experienced household food insecurity; 19.3% of mothers whose responses to the Radimer/Cornell scale indicated individual food insecurity and 35.0% fell into the child hunger category. Compared to food-insecure households, food-secure households had significantly higher total food expenditures (p<0.05), which include expenditures on fruits and vegetables (p = 0.011), animal-source food (p = 0.028) and milk and dairy products (p = 0.047). Furthermore, compared to their counterparts in the food-secure group, mothers from food-insecure households had lower diet diversity scores on grain and cereals, meat and meat products, fish and seafood, fruits, vegetables, milk and dairy products and beverages. Multinomial logistic regression revealed that total food expenditure (OR = 0.99; 95% C.I, 0.99, 1.00; p<0.05) and total diet diversity score (OR = 0.63; 95% CI, 0.54, 0.75; p<0.001) were found to be associated with household food insecurity after controlling for potential confounder. The prevalence of household food insecurity has reached a high and alarming scale. Inadequate dietary intake is usually observed in low-income households as direct or indirect consequences of household food insecurity.